Human-Computer Systems Interaction Backgrounds and Applications 4 - Hippe, Zdzisław S.; Kulikowski, Juliusz L.; Mroczek, Teresa (Advances in Intelligent Systems and Computing, 2018)
This book presents a fascinating, state-of-the-art collection of papers on the recent advances in human-computer systems interaction (H-CSI). It offers a detailed description of the status quo in the H-CSI field and also provides a solid base for further development and research in the area. The content is divided into three parts: I. Aid systems for disabled people; II. Decision-making support systems; and III. Information and communication systems.  It is intended for a wide audience of readers who are not necessarily experts in computer science, machine learning or knowledge engineering, but are interested in human-computer systems interaction, and the combination of general and specific papers offers readers deeper insights than might be gleaned from research papers or talks at conferences. It touches on all the current hot topics in the field of H-CSI.